Prime Human Resource Management Implementation, Work Performance, and Client Satisfaction in the City Government of Calamba - Lopez, Jenny Rose (Journal of Interdisciplinary Perspectives, 2024)
In today's government landscape, the need to possess expertise in Human Resource Management (HRM) and adhere to the ideals of meritocracy has become highly significant. PRIME-Human Resource Management plays a crucial role in optimizing staff performance through its holistic approach. It is imperative to conduct a comprehensive study on the complex connection between PRIME-HRM, performance, and customer satisfaction, especially in the specific setting of city government, as exemplified by the case of Calamba. The research investigated the relationships between the level of implementation of PRIME-HRM and the level of work performance, and how work performance, in turn, affected client satisfaction in the City Government of Calamba. Additionally, the study discussed the issues, concerns, and difficulties that hinder meeting the goals of PRIME-HRM implementation, increased work performance, client satisfaction, and retention. A researcher-made and adopted questionnaire was used to collect data from 201 randomly selected respondents. The model was analyzed using the Mean, Four-point Likert Scale, Standard Deviation, and Pearson Product-moment Correlation. The analysis revealed a significant relationship between the level of implementation of PRIME-HRM and Work Performance and no significant relationship between frontline employees' work performance and client satisfaction. Furthermore, the study proposed an action plan to develop, improve, and incorporate more techniques into the ongoing implementation of PRIME-HRM to enhance the current program and increase employee performance and client satisfaction. The strategies and activities like streamlining and establishing and oversight committee were proposed to include more techniques in the ongoing implementation of PRIME-HRM to enhance the current program and increase employee performance and client satisfaction.